Judicial Review and the Role of the Judiciary in Dutch Constitutional Law - Pieter Van Den Berg (IJOLARES: Indonesian Journal of Law Research, 2025)
This article discusses the concept of judicial review and the role of the judiciary within the Dutch constitutional law system, which constitutionally prohibits courts from reviewing the constitutionality of statutes through Article 120 of the Grondwet (Dutch Constitution). However, in practice, various indirect mechanisms allow for the continued exercise of judicial oversight over legislation. This article aims to examine how judicial institutions in the Netherlands contribute to constitutional oversight despite the formal prohibition of judicial review. The main research question explored is: How do judicial institutions in the Netherlands fill the void left by the absence of constitutional judicial review?. The article employs a normative and comparative approach. The comparative element involves both an internal comparison—between legal norms and judicial practices within the Netherlands—and an external comparison with selected foreign constitutional systems that permit judicial review. The approach is not limited to doctrinal analysis; it also incorporates secondary data drawn from court practices and legal developments in case law. The role of the Raad van State as a legislative advisor and administrative court, as well as the Hoge Raad as the Supreme Court that develops progressive legal interpretations, serves as a key instrument in controlling the quality of regulations. In addition, Dutch national courts also invoke international law—particularly the European Convention on Human Rights (ECHR)—as a basis for refusing to apply national laws that conflict with human rights, pursuant to Article 94 of the Grondwet.